2002
DOI: 10.1152/japplphysiol.00668.2001
|View full text |Cite
|
Sign up to set email alerts
|

Human neuromuscular fatigue is associated with altered Na+-K+-ATPase activity following isometric exercise

Abstract: The purpose of this study was to investigate the hypothesis that reductions in Na+-K+- ATPase activity are associated with neuromuscular fatigue following isometric exercise. In control (Con) and exercised (Ex) legs, force and electromyogram were measured in 14 volunteers [age, 23.4 ± 0.7 (SE) yr] before and immediately after (PST0), 1 h after (PST1), and 4 h after (PST4) isometric, single-leg extension exercise at ∼60% of maximal voluntary contraction for 30 min using a 0.5 duty cycle (5-s contraction, 5-s re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
89
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 46 publications
9
89
0
2
Order By: Relevance
“…The potentiated twitch force, which can be isolated to the muscle, is used to adjust the calculation of %ACT of muscle by the neural system. All of these procedures have been previously described in detail by our group (21,55).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The potentiated twitch force, which can be isolated to the muscle, is used to adjust the calculation of %ACT of muscle by the neural system. All of these procedures have been previously described in detail by our group (21,55).…”
Section: Participantsmentioning
confidence: 99%
“…During a typical test session, subjects were first assessed for supramaximal twitch properties, followed by tetanic stimulations from low to high frequency and concluding with MVCs. All procedures for calculation of specific properties are as previously detailed (21).…”
Section: Participantsmentioning
confidence: 99%
“…50 % of the highest registered MVC was the force used in the fatiguing task. After 50 % MVC was calculated, participants completed a fatiguing protocol with a 0.5 duty cycle where they pinched the force transducer for five seconds (contraction time) to 50 % MVC then released it for five seconds (relaxation time) in a continuous cycle for 15 minutes (modified from Fowles et al, 2002). A visual display was available to assist participants with matching the required force output.…”
Section: Fatiguing Protocolmentioning
confidence: 99%
“…The fatiguing protocol was to be aggressive enough to elicit an increased level of low frequency fatigue as the effects of this type of fatigue last longer than those of high frequency fatigue (Edwards et al, 1977;Fuglevand et al, 1999;Lehman, 1997;Schwendner et al, 1995). The fatiguing protocol used in this experiment has been validated and used in studies evaluating the vastus lateralis musculature of the leg (Fowles et al, 2002). It would be beneficial to validate the protocol for use with a precision grasp, but because of the complicated anatomy of the human hand, it was difficult to isolate the muscles involved by means of superficial stimulation techniques.…”
Section: Nature Of Fatiguing Protocolmentioning
confidence: 99%
“…The vectorial transport of Na + and K + across the sarcolemma by pump function restores ionic gradients after action potential 14) . Previous studies showed that Na + -K + -ATPase activity was reduced with heavy isometric 15) , isokinetic 16) , and progressive exercise 17) . ECC might elicit the formation of abnormal membranes that are involved in the excitation-contraction coupling process 18) and the pronounced increases in intracellular Na + concentration ([Na + ]i) 19) by Na + entry through ECC-induced fiber muscle membrane disruption and t-tubule tears 5) or the opening of stretch-sensitive cation channels 5,6) .…”
Section: Introductionmentioning
confidence: 97%